1995
DOI: 10.1046/j.1471-4159.1995.64031197.x
|View full text |Cite
|
Sign up to set email alerts
|

[3H]Paroxetine Binding Is Altered in the Hippocampus but Not the Frontal Cortex or Caudate Nucleus from Subjects with Schizophrenia

Abstract: [3H]Paroxetine binding to particulate membrane from tissue, obtained at autopsy, from the hippocampus, frontal cortex, and caudate nucleus from subjects who had or had not had schizophrenia was measured. The density of [3H]paroxetine binding to membranes from subjects who had or had not had schizophrenia did not differ. Similarly, the affinity of [3H]paroxetine binding in the frontal cortex and caudate nucleus was not different. By contrast, the affinity of [3H]paroxetine binding to hippocampal membrane from s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(16 citation statements)
references
References 13 publications
3
13
0
Order By: Relevance
“…Two studies reported a decrease in SERT density in the frontal cortex of individuals with schizophrenia, 99,100 whereas two studies reported no change in this region. 101,102 Decreased SERT density has also been reported in the cingulate cortex in one study. 102 SERT density has been reported as unchanged in other cortical regions-namely, the parietal, 99,101 temporal, 99 and occipital cortices.…”
Section: Serotonin Transportersmentioning
confidence: 69%
See 2 more Smart Citations
“…Two studies reported a decrease in SERT density in the frontal cortex of individuals with schizophrenia, 99,100 whereas two studies reported no change in this region. 101,102 Decreased SERT density has also been reported in the cingulate cortex in one study. 102 SERT density has been reported as unchanged in other cortical regions-namely, the parietal, 99,101 temporal, 99 and occipital cortices.…”
Section: Serotonin Transportersmentioning
confidence: 69%
“…101,102 Decreased SERT density has also been reported in the cingulate cortex in one study. 102 SERT density has been reported as unchanged in other cortical regions-namely, the parietal, 99,101 temporal, 99 and occipital cortices. 100 Limited information is available for subcortical regions: for the striatal regions, one study reported no change in SERT density in the caudate, 102 but one study reported an increased SERT density in the caudate, nucleus accumbens, and putamen.…”
Section: Serotonin Transportersmentioning
confidence: 69%
See 1 more Smart Citation
“…Two postmortem studies applying [ 3 H]cyano-imipramine and [ 3 H]paroxetine have initially shown that the density of SERT is decreased in the frontal cortex (Joyce et al, 1993;Laruelle et al, 1993a (Dean et al, 1995;Naylor et al, 1996;Gurevich and Joyce, 1997;Dean et al, 1999b). In fact, three of these studies did not report altered SERT densities but did find a decrease in the affinity of [ 3 H]paroxetine for SERT in hippocampal membranes, whereas the affinity of [ 3 H]paroxetine for SERT binding in the frontal cortex was unaltered (Dean et al, 1995Naylor et al, 1996). Gurevich and Joyce (Gurevich and Joyce, 1997) concluded that the initial positive findings were probably confounded by a large amount of schizophrenia patients who committed suicide in the samples.…”
Section: Serotonin Transporter (Sert)mentioning
confidence: 99%
“…The 5-HTT acts as a binding site for tricyclic and selective serotonin reuptake inhibitor antidepressants, as well as several drugs of abuse including cocaine (Langer et al, 1980;Rudnick and Wall, 1992). This reuptake system also has a role in agerelated neurodegenerative disorders including schizophrenia (Dean et al, 1995), Alzheimer (Chinaglia et al, 1993), and Parkinson (Raisman et al, 1986) diseases. Although the serotonergic system has been implicated in age-dependent central nervous system (CNS) pathologies, studies on the cellular, molecular, and physiological profile of the aging hippocampal 5-HT system are limited and often conflicting.…”
Section: Introductionmentioning
confidence: 99%